1991
DOI: 10.1159/000247731
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Kinetics of Human Anagen Scalp Hair Bulbs in Thyroid Disorders Determined by DNA Flow Cytometry

Abstract: In both, 6 hyperthyroid and 6 hypothyroid patients as well as 10 healthy volunteers, cell cycle kinetics of dissected anagen scalp hair bulbs were determined by means of DNA flow cytometry (DNA-FCM). Compared with the healthy control group in patients with thyroid disorders striking differences of cell kinetic data were evaluated. In hyperthyroidism a significant increase (30%) and in hypothyroidism a significant decrease (15%) of S and G2 + M phase cell percentages was found. The proliferation inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…Our demonstration that addition of exogenous TH to human HFs cultured in the absence of systemic TH prolongs anagen and stimulates hair matrix keratinocyte proliferation and inhibits their apoptosis provides the first direct evidence for the validity of this old postulate. Our findings also fit well with the reportedly increased hair matrix proliferation in hyperthyroid patients in vivo (3). Unfortunately, amputated, organcultured human scalp anagen VI hair bulbs do not run through full cycles in vitro and decay shortly after catagen development (30,(37)(38)(39).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our demonstration that addition of exogenous TH to human HFs cultured in the absence of systemic TH prolongs anagen and stimulates hair matrix keratinocyte proliferation and inhibits their apoptosis provides the first direct evidence for the validity of this old postulate. Our findings also fit well with the reportedly increased hair matrix proliferation in hyperthyroid patients in vivo (3). Unfortunately, amputated, organcultured human scalp anagen VI hair bulbs do not run through full cycles in vitro and decay shortly after catagen development (30,(37)(38)(39).…”
Section: Discussionsupporting
confidence: 89%
“…HFs were washed several times and cultured for 48 h. Serum-free supernatant was collected for the analysis. The sensitivity of the assays was 0.260 pg/ml (0.400 pmol/liter) for fT 3 and 0.23 pg/ml (0.30 pmol/liter) for fT 4 .…”
Section: Free T 3 (Ft 3 ) and Ft 4 Immunoassaymentioning
confidence: 96%
“…Massive telogen effluvium may occur when there is abrupt onset of hypothyroidism, and the percentage of scalp hairs in telogen is generally increased in hypothyroid states [10]. Using DNA flow cytometry, Schell et al observed that cell proliferation indices were reduced in hair bulbs of hypothyroid subjects and increased in hyperthyroidism compared with normal values [13]. Hypothyroid patients, especially children, frequently develop long, lanugo-type hair on the back, shoulders, and extremities [10].…”
Section: Introductionmentioning
confidence: 99%
“…DNA flow cytometry studies of dissected anagen hairs from thyrotoxic patients (compared with follicles taken from euthyroid controls) demonstrated a 30% increase in the S and G 2 + M phases of the cell cycle. 52 However, like with epidermal proliferation, hair changes with thyrotoxicosis are different than what can be effected with topically administered thyroid hormone. Mice and rats treated daily for 1-2 weeks with topical T 3 had increased hair counts but mice made thyrotoxic with daily intraperitoneal T 3 for 1-2 weeks had decreased hair counts.…”
Section: Skin Manifestation Of Thyroid Hormone Action On Other Tissuesmentioning
confidence: 99%